2009
DOI: 10.1590/s1516-35982009000200013
|View full text |Cite
|
Sign up to set email alerts
|

Available phosphorus levels in diets for swine from 15 to 30 kg genetically selected for meat deposition

Abstract: -With the objective to evaluate available phosphorus levels in diets for swine genetically selected for meat deposition, sixty commercial hybrid pigs were used, being 30 castrate males and 30 females, with initial weight of 15.00 ± 0.41 kg, distributed in a completely randomized experimental design, with six treatments, five replications and two animals (1 male and 1 female) per experimental unit. The treatments were composed of a basal diet and other five diets obtained through basal diet supplementation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
2
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 18 publications
5
20
2
7
Order By: Relevance
“…On the other hand, Eeckhout et al (1995) and Saraiva et al (2009b) assessing different dietary aP levels for 37 to 61 kg and 15 to 30 kg pigs, respectively, verified that voluntary feed intake of pigs increased linearly with increasing aP in the diets. Unlike, Ketaren et al (1992), Ekpe (2002), and Arouca et al(2010) working with growing pigs fed different dietary aP, found that the ADFi of the animals showed a quadratic behavior up to the maximum estimated levels of 0.300, 0.350, and 0.430% aP.…”
Section: Methodsmentioning
confidence: 86%
“…On the other hand, Eeckhout et al (1995) and Saraiva et al (2009b) assessing different dietary aP levels for 37 to 61 kg and 15 to 30 kg pigs, respectively, verified that voluntary feed intake of pigs increased linearly with increasing aP in the diets. Unlike, Ketaren et al (1992), Ekpe (2002), and Arouca et al(2010) working with growing pigs fed different dietary aP, found that the ADFi of the animals showed a quadratic behavior up to the maximum estimated levels of 0.300, 0.350, and 0.430% aP.…”
Section: Methodsmentioning
confidence: 86%
“…1). Stahly et al (2000), Arouca (2008), Saraiva et al (2009a) Figura 1. Ganho de peso diário de suínos dos 15 aos 30kg, segundo a concentração de fósforo disponível na dieta.…”
Section: Resultsunclassified
“…Hastad et al (2004), ao avaliarem porcentagens de Pd variando entre 0,180 e 0,320%, também não verificaram efeito sobre a RO e a CO, avaliadas no terceiro e quarto metatarsos. De forma diferente, Arouca (2008) e Saraiva et al (2009a) constataram efeito linear crescente, enquanto O'Quinn et al (1997) e Saraiva et al (2009b) verificaram efeito quadrático sobre a resistência óssea.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…SARAIVA et al (2009b), trabalhando com níveis de fósforo disponível variando de 0,114 a 0,649%, em rações de suínos dos 15 aos 30 kg, observaram aumento linear no consumo de ração com o aumento nos níveis de fósforo.…”
Section: Resultsunclassified